Antisecretory Factor May Reduce ICP in Severe TBI—A Case Series - Cederberg, David; Hansson, Hans-Arne; Visse, Edward; Siesjö, Peter (Frontiers in Neurology, 2020)
Traumatic brain injury (TBI) constitutes a global epidemic. Overall outcome is poor with mortality ranging from 10-70 % and significant long term morbidity. Several experimental reports have claimed effect on traumatic edema but all clinical trials have failed. Antisecretory factor, an endogenous protein, is commercially available as Salovum®, which is classified as a medical food by the European Union and has been proven effective in experimental trauma models. It has however, previously not been tested in humans with severe TBI. We hereby report a case series of 5 adult patients with severe TBI, treated with Salovum®. The objective of the intervention was to evaluate safety and its effect on intracranial pressure and outcome. Patients received 1 g Salovum® per kilo body weight divided into 6 doses per 24 hours. Each dose administered through the nasogastric tube. Patients were scheduled for 5 days of treatment with Salovum®. Intracranial pressure was controlled, except for during periods of gastro-paresis. 5/5 patients had a favorable short term outcome and 4/5 patients had a favourable long term outcome. No toxicity was observed. We conclude that all five treated patients experienced an effect of Salovum® with a clear reduction of intracranial pressure and signs of clinical benefit. In order to validate the potential of anti-secretory factor in TBI, a prospective, randomized, double-blinded, placebo-controlled trial with Salovum has been initiated. Primary outcome for the trial is 30-day mortality, secondary outcomes are treatment intensity level, intracranial pressure, and number of days at NICU.